Factors associated with adherence of hypertensive and diabetic patients to the use of medication from the pictographic prescription (Research, Society and Development, 2023)
Objective: to evaluate the factors associated with adherence of hypertensive and diabetic patients to the use of medications and the impact of pictorial prescription on treatment adherence. Methods: an integrative literature review was conducted. Articles retrieved from the secondary databases Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (Scielo) and Online System for Search and Analysis of Medical Literature (MEDLINE) were analyzed using the descriptors chronic non-communicable diseases; systemic arterial hypertension; diabetes and medication adherence. We considered studies published in Portuguese, English or Spanish and that dealt directly with the theme object of study. Results: the factors associated with adherence of hypertensive and diabetic patients may be individual, related to treatment, the disease and the health institution, illiteracy and cognitive difficulties are presented as barriers to medication adherence in some cases, in this sense, the use of pictography, non-verbal language, use of colors, among other technologies can add to the quality of life of patients. Conclusion: the factors associated with medication adherence are complex and this care technology favors adherence to drug treatment by patients with diabetes and hypertension and can be used by professionals in the routine of the service, provided that it is monitored systematically and with the support of the entire team.